Dimensions of the third. On the entanglement between landscape, body and atmosphere (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Landscape, body and atmosphere form a triad and must be conceived as peculiar dimensions of the ‘third’ and, at the same time, in their fundamental and original connection. They are ontological phenomena, groundless reasons, or anarchic elements and the silent prerequisites of world experience. The present article explores the concept of the ‘third’ and describes the constellation between the landscape, the body and the atmosphere in dialogue with authors like Gernot Böhme, Gilles Clément and Graham Harman. This explanation leads us to think about the political consequences of reconsidering the third and to develop a specific ‘Politics of the Sensible’. It is the task of the ‘Politics of the Sensible’ to recover what has fallen under the ruins of history, under the pharaonic construction of our civilization: to signify and develop the body’s own innate and learned sensibility and our vital relation with Earth.